Preparation method of conductive and magnetic conductive ceramic based on iron tailings
By introducing the iron germ powder of the foaming agent and conductive magnetic conductivity in the ceramic sintering formula, prepare a simple and low -cost conductive magnetic conductor -conducting ceramics, and solve the difficulty of using iron tail mine sintering ceramics and ultra -fine tail mine powder. The problem has realized the new functional characteristics and wide application of ceramics.
Patent Information
- Application Number
- CN202411458075.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, iron tailings sintered ceramics are prone to foaming, and ultrafine tailings powder is difficult to effectively utilize, resulting in high costs and environmental pollution.
By introducing a defoaming agent into the ceramic sintering formula, and adding conductive and magnetically conductive iron powder and a sintering aid, the conductive and magnetically conductive ceramics are prepared using the processes of mixing, granulation, dry pressing and sintering.
The well -conductive magnetic ceramics preparation with a simple and low cost, the problem of ceramic foaming, and given new functional characteristics of ceramics, suitable for applications such as antistatic and electromagnetic shielding.
Smart Images

Figure CN119330685A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special ceramic preparation, and in particular relates to a method for preparing conductive and magnetic ceramics based on iron tailings. Background Art
[0002] Environment and development have always been the themes of modern society. With the advancement of science and technology, while human life has improved, new environmental problems caused by waste generated in the production process and new products and life have also troubled people. While people enjoy the convenient life brought by the development of electronic information, they also bring potential hazards of electromagnetic radiation. While people obtain a large number of metal products, a large amount of waste caused by mineral mining also threatens the living environment of human beings. Therefore, with the development of society, people's understanding of environmental protection is becoming more and more profound, and the requirements are becoming more and more urgent.
[0003] Hebei Province is an important iron ore producing area and steel producing province in my country, with more than 1,000 iron mines of various sizes. For most mines, the tailings pond capacity has long been unable to accommodate the tailings discharge of super-long service life, and the tailings pond stacking problem needs to be solved urgently. The comprehensive utilization of mine waste is the ultimate direction to solve the problem, especially the utilization of ultra-fine tailings powder that is not suitable for stacking and landfilling is the top priority. Among the products produced by iron ore, they can be divided into iron ore powder and tailings. Usually, iron ore powder is the final product of the mine. And the tailings are divided into those that can be used at this stage, such as rough stone, and coarse-grained tailings powder can be used as infrastructure materials. For ultra-fine tailings powder, no matter what stacking and landfilling method is used, it is a thorny problem. A large amount of adhesive is required, which greatly increases the cost and makes it difficult for enterprises to bear. If handled improperly, it is very easy to cause loss and cause the risk of dam collapse under the scouring of water flow. In addition, ultra-fine tailings powder is suspended in water and it is difficult to precipitate quickly. The application of a large amount of flocculants will not only increase the cost but also bring new environmental pollution.
[0004] The biggest problem of iron tailings sintered ceramics is that the tailings contain a large amount of iron elements, which easily cause ceramic foaming during the sintering process. Therefore, an important step in the preparation process of daily-use ceramics is iron removal. The present invention introduces a defoaming agent into the ceramic sintering formula to eliminate the ceramic foaming problem during the sintering process, so a large amount of iron concentrate can be introduced to give the ceramic new functional properties. Summary of the invention
[0005] Aiming at the shortcomings of the prior art, especially the high iron body sintering process is very easy to bubble, and the general ceramics are not conductive and magnetic. The purpose of the present invention is to provide a method for producing conductive and magnetic ceramics with simple process, low cost and good performance. The method uses iron tailings as the main raw material, adds conductive and magnetic iron concentrate, defoaming agent and sintering aid, mixes, granulates, and forms blanks, and then sinters to produce conductive and magnetic ceramics.
[0006] A method for preparing a conductive and magnetic ceramic based on iron tailings, specifically comprising the following steps:
[0007] (1) Using fine iron tailings powder as a base material, adding a conductive agent, a plasticizer, a sintering aid and a defoaming agent as auxiliary materials, and then adding a binder, uniformly mixing, and granulating to obtain a ceramic granulated material;
[0008] (2) dry-pressing the granulated material obtained in step (1) to obtain a ceramic body;
[0009] (3) Sintering the ceramic body to obtain a ceramic product.
[0010] in:
[0011] In the step (1), the content of each component is calculated by mass fraction: 30% to 85% of fine iron tailings powder, 15% to 65% of conductive agent, 3% to 15% of plasticizer, 0% to 5% of sintering aid, and 0.01% to 5% of defoaming agent, totaling 100%.
[0012] In the step (1), the amount of the adhesive added is 5% to 8% of the total mass of the base material and the auxiliary materials.
[0013] In the step (1), the particle size of the fine iron tailings powder is less than 1 mm; the chemical composition of the fine iron tailings powder is as follows, by mass fraction: SiO2 30% to 70%, Fe3O4≤20%, CaO 2% to 25%, A12O3 3% to 9%, MgO 0.1% to 15%, Na2O≤2%, and K2O≤2%.
[0014] In the step (1), the conductive agent is a combination of one or more of M and one or two of F, and the mass ratio of M to F is (0-1):1, wherein M is MnO2, ZnO, NiO, TiO2 and MgO, and F is CuO, Fe3O4 and Fe2O3.
[0015] In the step (1), the plasticizer is clay and / or talc, the sintering aid is feldspar and / or glass powder, and the defoaming agent is one or more combinations of MgO, TiO2, ZnO, and CaCO3.
[0016] In the step (2), the pressure of dry pressing is 0.1 to 10 MPa.
[0017] In the step (3), the sintering process is atmospheric pressure sintering, atmosphere sintering or hot pressing sintering.
[0018] In the step (3), the sintering temperature is 1000-1150° C., the heating rate is 2-20° C. / min, and the sintering holding time is 0.5-5 h.
[0019] In the step (3), the water absorption rate of the ceramic is 0.003% to 5%, and the Vickers hardness is 800 to 1500 kgf / mm 2 , the resistivity is 10 3 ~10 9 Ω·cm, magnetic permeability is 2~250.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The method provided by the present invention has simple process and low cost. The obtained conductive and magnetic ceramics have excellent performance. A defoaming agent is introduced into the sintering formula of the ceramic to eliminate the foaming problem of the ceramic during the sintering process. Furthermore, a large amount of iron ore powder can be introduced into the formula to give the ceramics new functional properties.
[0022] 2. The base material of the present invention adopts ultra-fine tailing powder, which has high sintering activity. By adding conductive and magnetic iron concentrate, defoamer and sintering aid into the base material, it is sintered into conductive and magnetic ceramics, which can be applied to antistatic tiles and electromagnetic shielding tiles. It has a wide range of application value in industrial and mining enterprises, national defense, aerospace, aviation and civil homes. Therefore, it is of great significance both in terms of the necessity of dissolving ultra-fine tailing powder and the conductive and magnetic ceramic products developed. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD patterns of the conductive and magnetic ceramics prepared in Examples 1, 2 and 3 of the present invention;
[0024] Figure 2 SEM image of the conductive and magnetic ceramics prepared in Example 1 of the present invention;
[0025] Figure 3 XRD patterns of the conductive and magnetic ceramics prepared in Examples 4, 5 and 6 of the present invention;
[0026] Figure 4 SEM image of the conductive and magnetic ceramics prepared in Example 4 of the present invention;
[0027] Figure 5 XRD patterns of the conductive and magnetic ceramics prepared in Examples 7, 8 and 9 of the present invention;
[0028] Figure 6 SEM image of the conductive and magnetic ceramic prepared in Example 7 of the present invention. DETAILED DESCRIPTION
[0029] In the embodiment of the present invention, the minerals in the fine-grained iron tailings powder used are quartz, pyroxene, feldspar, garnet, amphibole, altered minerals and residual hematite or magnetite. Calculated by mass fraction, the chemical components contained in the minerals are: SiO2~70%, Fe3O4≤10%, CaO~5%, A12O3~9%, MgO~5%, Na2O≤2%, K2O≤2%, wherein the silicon dioxide contained in the feldspar acts as a sintering aid.
[0030] In the embodiment of the present invention, the adhesive used is polyvinyl alcohol with a mass concentration of 8%.
[0031] Example 1
[0032] A method for preparing a conductive and magnetic ceramic based on iron tailings, specifically comprising the following steps:
[0033] (1) Weigh 9 g of ultrafine iron tailings powder sieved with 100 mesh after ball milling and 1 g of clay, mix and ball mill, and then dry, add 4 g of iron concentrate (magnetite concentrate powder, Fe3O4) and 0.1 g of MgO as auxiliary materials, and then add 0.7 g of polyvinyl alcohol as a binder, mix well and granulate to obtain ceramic granules; wherein the iron concentrate acts as a conductive agent and the MgO acts as a defoaming agent;
[0034] (2) dry-pressing the granulated material obtained in step (1) at a pressure of 1 MPa to obtain a ceramic body;
[0035] (3) The ceramic body is placed in a tubular furnace and sintered at 1050°C under normal pressure in a nitrogen atmosphere, with a heating rate of 5°C / min and a holding time of 2h. The ceramic body is then cooled to room temperature to obtain a conductive and magnetic ceramic. The water absorption of the ceramic is 0.3% and the Vickers hardness is 950kgf / mm. 2 , the magnetic permeability is ~150.
[0036] The XRD characteristics of the obtained conductive and magnetic ceramics are as follows: Figure 1 As shown in the figure, it can be seen that the main component phases of the sintered ceramic sample are pure iron obtained by reducing iron concentrate in a reducing atmosphere. At the same time, the pure iron plays a conductive role as the main conductive phase in the conductive ceramic. In addition to the main conductive phase of pure iron, the sample also contains SiO2, the main raw material phase of the ceramic, and Fe2SiO4, Na (AlSi3O8) and other phases obtained after sintering the ultrafine iron tailings powder raw material.
[0037] The SEM images of the obtained conductive and magnetic ceramics are as follows: Figure 2As shown in the figure, the microstructure of the sample is an irregular block structure with spherical micro-protrusions on the surface. Although there are a certain number of pores, the grains are relatively densely bonded and the grains are interconnected. Therefore, the sample has conductive properties. The resistivity of the ceramic sample is 1.4×10 6 Ω·cm, suitable as a high resistance heating element. It has magnetic properties and can also be used as an electromagnetic shielding material and antistatic material.
[0038] Example 2
[0039] A method for preparing a conductive and magnetic ceramic based on iron tailings, specifically comprising the following steps:
[0040] (1) Weigh 9 g of ultrafine iron tailings powder sieved with 100 mesh after ball milling and 1 g of clay, mix and ball mill and then dry, add 4 g of iron concentrate (magnetite concentrate powder, Fe3O4) and 0.2 g of CaCO3 as auxiliary materials, and then add 0.7 g of polyvinyl alcohol as a binder, mix well and then granulate to obtain ceramic granules, wherein the iron concentrate acts as a conductive agent and the CaCO3 acts as a defoaming agent;
[0041] (2) dry-pressing the granulated material obtained in step (1) at a pressure of 1 MPa to obtain a ceramic body;
[0042] (3) The ceramic body is placed in a tubular furnace and sintered at 1070°C under normal pressure in a nitrogen atmosphere, with a heating rate of 5°C / min and a holding time of 2h. The ceramic body is then cooled to room temperature to obtain a conductive and magnetic ceramic. The water absorption of the ceramic is 0.2% and the Vickers hardness is 1000kgf / mm. 2 , the magnetic permeability is 180.
[0043] The XRD characteristics of the obtained conductive and magnetic ceramics are as follows: Figure 1 As shown in the figure, it can be seen that the main component phase of the sintered ceramic sample is pure iron obtained by reducing iron concentrate in a reducing atmosphere. At the same time, the pure iron plays a conductive role as the main conductive phase in the conductive ceramic. In addition to the main conductive phase of pure iron, the sample also contains SiO2, the main raw material phase of the ceramic, and Fe2SiO4, Na (AlSi3O8) and other phases obtained after sintering the ultrafine iron tailings powder raw material.
[0044] SEM and Figure 2 Similarly, the microstructure of this sample is an irregular block structure with spherical micro-protrusions on the surface. Although there are a certain number of pores, the grains are relatively densely bonded and the grains are interconnected. Therefore, this sample has conductive properties. The resistivity of this ceramic sample is 1.2×10 6Ω·cm, suitable as a high resistance heating element. It has magnetic properties and can also be used as an electromagnetic shielding material and antistatic material.
[0045] Example 3
[0046] A method for preparing conductive and magnetic ceramics based on iron tailings, specifically comprising the following steps:
[0047] (1) Weigh 9 g of ultrafine iron tailings powder sieved with 100 mesh after ball milling and 1 g of clay, mix and ball mill and then dry, add 4 g of iron concentrate (magnetite concentrate, Fe3O4) and 0.15 g of MgO as auxiliary materials, and then add 0.7 g of polyvinyl alcohol as a binder, mix well and granulate to obtain ceramic granules; wherein the iron concentrate acts as a conductive agent and the MgO acts as a defoaming agent;
[0048] (2) dry-pressing the granulated material obtained in step (1) at a pressure of 1 MPa to obtain a ceramic body;
[0049] (3) The ceramic body is placed in a tubular furnace and sintered at 1100°C under normal pressure in a nitrogen atmosphere, with a heating rate of 5°C / min and a holding time of 2h. The ceramic body is then cooled to room temperature to obtain a conductive and magnetic ceramic. The water absorption of the ceramic is 0.1% and the Vickers hardness is 1250kgf / mm. 2 , the magnetic permeability is ~200.
[0050] The XRD characteristics of the obtained conductive and magnetic ceramics are as follows: Figure 1 As shown in the figure, it can be seen that the main component phase of the sintered ceramic sample is pure iron obtained by reducing iron concentrate in a reducing atmosphere. At the same time, the pure iron plays a conductive role as the main conductive phase in the conductive ceramic. In addition to the main conductive phase of pure iron, the sample also contains SiO2, the main raw material phase of the ceramic, and Fe2SiO4, Na (AlSi3O8) and other phases obtained after sintering the ultrafine iron tailings powder raw material.
[0051] SEM and Figure 2 Similarly, the microstructure of this sample is an irregular block structure with spherical micro-protrusions on the surface. Although there are a certain number of pores, the grains are relatively densely bonded and the grains are interconnected. Therefore, this sample has conductive properties. The resistivity of this ceramic sample is 1.0×10 6 Ω·cm, suitable as a high resistance heating element. It has magnetic properties and can also be used as an electromagnetic shielding material and antistatic material.
[0052] Example 4
[0053] A method for preparing conductive and magnetic ceramics based on iron tailings, specifically comprising the following steps:
[0054] (1) Weigh 9 g of ultrafine iron tailings powder that has been ball-milled and sieved to 100 mesh and 1 g of clay, mix and ball-mill, and then dry, add 2.5 g of CuO and 0.05 g of ZnO as auxiliary materials, and then add 0.625 g of polyvinyl alcohol as a binder, mix well and then granulate to obtain a ceramic granulate, wherein CuO acts as a conductive agent and ZnO acts as a defoaming agent;
[0055] (2) dry-pressing the granulated material obtained in step (1) at a pressure of 1 MPa to obtain a ceramic body;
[0056] (3) The ceramic body is placed in a muffle furnace and sintered at 1060°C under normal pressure in air, with a heating rate of 5°C / min and a holding time of 2h. The ceramic body is then cooled to room temperature to obtain a conductive and magnetic ceramic. The water absorption of the ceramic is 0.5% and the Vickers hardness is 1100kgf / mm 2 , the magnetic permeability is ~5.
[0057] The XRD characteristics of the obtained conductive and magnetic ceramics are as follows: Figure 3 As shown in the figure, it can be seen that the main component phase in the ceramic sample is CuFe2O4 generated by the reaction of iron ore concentrate and CuO in an oxidizing atmosphere, and the phases that play a conductive role in the conductive ceramic are CuFe2O4 and CuO. In addition to the main conductive phase CuFe2O4, the sample also contains SiO2, the main raw material phase of the ceramic, and a part of CuO that has not reacted completely.
[0058] SEM images of conductive and magnetic ceramics Figure 4 As shown, it can be seen that the microstructure of the sample is a lamellar structure, and the lamellar layers are directly stacked and connected to each other, making the sample conductive. The resistivity of the ceramic sample is 1.85×10 6 Ω·cm, suitable as a high resistance heating element. It has magnetic properties and can also be used as an electromagnetic shielding material and antistatic material.
[0059] Example 5
[0060] A method for preparing a conductive and magnetic ceramic based on iron tailings, specifically comprising the following steps:
[0061] (1) Weigh 9 g of ultrafine iron tailing powder sieved after ball milling and 1 g of clay, mix and ball mill, and then dry, add 2.7 g of CuO and 0.1 g of CaCO3 as auxiliary materials, and then add 0.635 g of polyvinyl alcohol as a binder, mix well and granulate to obtain ceramic granules; wherein CuO acts as a conductive agent and CaCO3 acts as a defoaming agent;
[0062] (2) dry-pressing the granulated material obtained in step (1) at a pressure of 1.5 MPa to obtain a ceramic body;
[0063] (3) The ceramic body is placed in a muffle furnace and sintered at 1060°C under normal pressure in air, with a heating rate of 5°C / min and a holding time of 2h. The ceramic body is then cooled to room temperature to obtain a conductive and magnetic ceramic. The water absorption of the ceramic is 0.5% and the Vickers hardness is 1150kgf / mm 2 , the magnetic permeability is ~10.
[0064] The XRD characteristics of the obtained conductive and magnetic ceramics are as follows: Figure 3 As shown in the figure, it can be seen that the main component phase in the ceramic sample is CuFe2O4 generated by the reaction of iron ore concentrate and CuO in an oxidizing atmosphere, and the phases that play a conductive role in the conductive ceramic are CuFe2O4 and CuO. In addition to the main conductive phase CuFe2O4, the sample also contains SiO2, the main raw material phase of the ceramic, and a part of CuO that has not reacted completely.
[0065] SEM and Figure 4 It can be seen that the microstructure of the sample is a lamellar structure, and the lamellar layers are directly stacked and connected to each other, making the sample conductive. The resistivity of the ceramic sample is 1.9×10 6 Ω·cm, suitable as a high resistance heating element. It has magnetic properties and can also be used as an electromagnetic shielding material and antistatic material.
[0066] Example 6
[0067] A method for preparing a conductive and magnetic ceramic based on iron tailings, specifically comprising the following steps:
[0068] (1) Weighing 9 g of ultrafine iron tailing powder sieved through 100 mesh after ball milling and 1 g of clay, mixing and ball milling, and then drying, adding 4 g of CuO and 0.1 g of MgO as auxiliary materials, and then adding 0.7 g of polyvinyl alcohol as a binder, fully mixing and then granulating to obtain ceramic granules; wherein CuO acts as a conductive agent, and MgO acts as a defoaming agent;
[0069] (2) dry-pressing the granulated material obtained in step (1) at a pressure of 2 MPa to obtain a ceramic body;
[0070] (3) The ceramic body is placed in a muffle furnace and sintered at 1060°C under normal pressure in air, with a heating rate of 5°C / min and a holding time of 2h. The ceramic body is then cooled to room temperature to obtain a conductive and magnetic ceramic. The water absorption of the ceramic is 0.15% and the Vickers hardness is 1300kgf / mm 2 , the magnetic permeability is ~15.
[0071] The XRD characteristics of the obtained conductive and magnetic ceramics are as follows: Figure 3 As shown in the figure, it can be seen that the main component phase in the ceramic sample is CuFe2O4 generated by the reaction of iron ore concentrate and CuO in an oxidizing atmosphere, and the phases that play a conductive role in the conductive ceramic are CuFe2O4 and CuO. In addition to the main conductive phase CuFe2O4, the sample also contains SiO2, the main raw material phase of the ceramic, and a part of CuO that has not reacted completely.
[0072] SEM and Figure 4 Similarly, the microstructure of this sample is a lamellar structure, and the lamellar layers are directly stacked and connected to each other, making the sample conductive. The resistivity of this ceramic sample is 1.0×10 6 Ω·cm, suitable as a high resistance heating element. It has magnetic properties and can also be used as an electromagnetic shielding material and antistatic material.
[0073] Example 7
[0074] A method for preparing a conductive and magnetic ceramic based on iron tailings, specifically comprising the following steps:
[0075] (1) 9 g of ultrafine iron tailings powder sieved through 100 mesh after ball milling and 1 g of clay were weighed, mixed and ball milled, and then dried. 2.5 g of CuO, 0.2 g of ZnO, and 15 g of iron concentrate (magnetite concentrate, Fe3O4) were added as auxiliary materials, and 1.385 g of polyvinyl alcohol was added as a binder. After being fully mixed, granulation was performed to obtain ceramic granules; wherein CuO and iron concentrate acted as conductive agents, and ZnO acted as a defoaming agent;
[0076] (2) dry-pressing the granulated material obtained in step (1) at a pressure of 1 MPa to obtain a ceramic body;
[0077] (3) The ceramic body is placed in a muffle furnace and sintered at 1060°C under normal pressure in air, with a heating rate of 5°C / min and a holding time of 2h. The ceramic body is then cooled to room temperature to obtain a conductive and magnetic ceramic. The water absorption of the ceramic is 0.05% and the Vickers hardness is 1200kgf / mm 2 , the magnetic permeability is ~20.
[0078] The XRD characteristics of the obtained conductive and magnetic ceramics are as follows: Figure 5As shown in the figure, it can be seen that the main component phases in the ceramic sample are CuFe2O4 generated by the reaction of iron ore concentrate and CuO in an oxidizing atmosphere. At the same time, the CuFe2O4 plays a conductive role as the main conductive phase in the conductive ceramic, and the residual CuO can also participate in the conduction. In addition to the main conductive phase CuFe2O4, the sample also contains SiO2, the main raw material phase of the ceramic, and a part of the unreacted CuO.
[0079] The SEM images of the obtained conductive and magnetic ceramics are as follows: Figure 6 As shown in the figure, it can be seen that the ceramic sample has a lamellar structure. The lamellar layers are directly stacked and connected to each other, making the sample conductive. The addition of ZnO makes the lamellar layers finer and the stacking and connection between the lamellar layers more dense. The resistivity of the ceramic sample is 0.14×10 6 Ω·cm, suitable as a high resistance heating element. It has magnetic properties and can also be used as an electromagnetic shielding material and antistatic material.
[0080] Example 8
[0081] A method for preparing conductive and magnetic ceramics based on iron tailings, specifically comprising the following steps:
[0082] (1) 9 g of ultrafine iron tailings powder sieved through 100 mesh after ball milling and 1 g of clay were weighed, mixed and ball milled, and then dried. 2.4 g of CuO, 0.3 g of ZnO, and 13 g of iron concentrate (magnetite concentrate, Fe3O4) were added as auxiliary materials, and 1.285 g of polyvinyl alcohol was added as a binder. After being fully mixed, granulation was performed to obtain ceramic granules; wherein CuO and iron concentrate acted as conductive agents, and ZnO acted as a defoaming agent;
[0083] (2) dry-pressing the granulated material obtained in step (1) at a pressure of 1.5 MPa to obtain a ceramic body;
[0084] (3) The ceramic body is placed in a muffle furnace and sintered at 1060°C under normal pressure in air, with a heating rate of 5°C / min and a holding time of 2h. The ceramic body is then cooled to room temperature to obtain a conductive and magnetic ceramic. The water absorption of the ceramic is 0.12% and the Vickers hardness is 1130kgf / mm 2 , the magnetic permeability is ~22.
[0085] The XRD characteristics of the obtained conductive and magnetic ceramics are as follows: Figure 5As shown in the figure, it can be seen that the main component phase in the ceramic sample is CuFe2O4 generated by the reaction of iron ore concentrate and CuO in an oxidizing atmosphere. At the same time, the CuFe2O4 plays a conductive role as the main conductive phase in the conductive ceramic, and the residual CuO can also participate in the conduction. In addition to the main conductive phase CuFe2O4, the sample also contains SiO2, the main raw material phase of the ceramic, and a part of the unreacted CuO.
[0086] SEM and Figure 6 Similarly, the ceramic sample has a lamellar structure. The addition of ZnO makes the lamellar structure finer and the stacking connection between the lamellar layers more dense. The resistivity of the ceramic sample is 0.2×10 6 Ω·cm, suitable as a high resistance heating element. It has magnetic properties and can also be used as an electromagnetic shielding material and antistatic material.
[0087] Example 9
[0088] A method for preparing a conductive and magnetic ceramic based on iron tailings, specifically comprising the following steps:
[0089] (1) 9 g of ultrafine iron tailings powder sieved through 100 mesh after ball milling and 1 g of clay were weighed, mixed and ball milled, and then dried. 2.2 g of CuO, 0.5 g of ZnO and 13 g of iron concentrate (magnetite concentrate, Fe3O4) were added thereto, and then 1.285 g of polyvinyl alcohol was added as a binder. After being fully mixed and uniformly granulated, ceramic granules were obtained; wherein CuO and iron concentrate acted as conductive agents, and ZnO acted as a defoaming agent;
[0090] (2) dry-pressing the granulated material obtained in step (1) at a pressure of 2 MPa to obtain a ceramic body;
[0091] (3) The ceramic body is placed in a muffle furnace and sintered at 1060°C under normal pressure in air, with a heating rate of 5°C / min and a holding time of 2h. The ceramic body is then cooled to room temperature to obtain a conductive and magnetic ceramic. The water absorption of the ceramic is 0.22% and the Vickers hardness is 1130kgf / mm 2 , the magnetic permeability is ~30.
[0092] The XRD characteristics of the obtained conductive and magnetic ceramics are as follows: Figure 5 As shown in the figure, it can be seen that the main component phase in the ceramic sample is CuFe2O4 generated by the reaction of iron ore concentrate and CuO in an oxidizing atmosphere. At the same time, the CuFe2O4 plays a conductive role as the main conductive phase in the conductive ceramic, and the residual CuO can also participate in the conduction. In addition to the main conductive phase CuFe2O4, the sample also contains SiO2, the main raw material phase of the ceramic, and a part of the unreacted CuO.
[0093] SEM and Figure 6 Similarly, the ceramic sample has a lamellar structure. The addition of ZnO makes the lamellar structure finer and the stacking connection between the lamellar layers more dense. The resistivity of the ceramic sample is 0.18×10 6 Ω·cm, suitable as a high resistance heating element. It has magnetic properties and can also be used as an electromagnetic shielding material and antistatic material.
Claims
1. A method for preparing a conductive and magnetic ceramic based on iron tailings, characterized in that: The specific steps include: (1) Using fine iron tailings powder as a base material, adding a conductive agent, a plasticizer, a sintering aid and a defoaming agent as auxiliary materials, and then adding a binder, uniformly mixing, and granulating to obtain a ceramic granulated material; (2) dry-pressing the granulated material obtained in step (1) to obtain a ceramic body; (3) Sintering the ceramic body to obtain a ceramic product.
2. The method for preparing a conductive and magnetic ceramic based on iron tailings according to claim 1, characterized in that: In the step (1), the content of each component is calculated by mass fraction: 30% to 85% of fine iron tailings powder, 15% to 65% of conductive agent, 3% to 15% of plasticizer, 0% to 5% of sintering aid, and 0.01% to 5% of defoaming agent, totaling 100%.
3. The method for preparing a conductive and magnetic ceramic based on iron tailings according to claim 1, characterized in that: In the step (1), the amount of the adhesive added is 5% to 8% of the total mass of the base material and the auxiliary materials.
4. The method for preparing a conductive and magnetic ceramic based on iron tailings according to claim 1, characterized in that: In the step (1), the particle size of the fine iron tailings powder is less than 1 mm; the chemical composition of the fine iron tailings powder is as follows, by mass fraction: SiO2 30% to 70%, Fe3O4≤20%, CaO 2% to 25%, A12O3 3% to 9%, MgO 0.1% to 15%, Na2O≤2%, and K2O≤2%.
5. The method for preparing a conductive and magnetic ceramic based on iron tailings according to claim 1, characterized in that: In the step (1), the conductive agent is a combination of one or more of M and one or two of F, and the mass ratio of M to F is (0-1):1, wherein M is MnO2, ZnO, NiO, TiO2 and MgO, and F is CuO, Fe3O4 and Fe2O3.
6. The method for preparing a conductive and magnetic ceramic based on iron tailings according to claim 1, characterized in that: In the step (1), the plasticizer is clay and / or talc, the sintering aid is feldspar and / or glass powder, and the defoaming agent is one or more combinations of MgO, TiO2, ZnO, and CaCO3.
7. The method for preparing a conductive and magnetic ceramic based on iron tailings according to claim 1, characterized in that: In the step (2), the pressure of dry pressing is 0.1 to 10 MPa.
8. The method for preparing a conductive and magnetic ceramic based on iron tailings according to claim 1, characterized in that: In the step (3), the sintering process is atmospheric pressure sintering, atmosphere sintering or hot pressing sintering.
9. The method for preparing a conductive and magnetic ceramic based on iron tailings according to claim 1, characterized in that: In the step (3), the sintering temperature is 1000-1150° C., the heating rate is 2-20° C. / min, and the sintering holding time is 0.5-5 h.
10. The method for preparing a conductive and magnetic ceramic based on iron tailings according to claim 1, characterized in that: In the step (3), the water absorption rate of the ceramic is 0.003% to 5%, and the Vickers hardness is 800 to 1500 kgf / mm 2 , the resistivity is 10 3 ~10 9 Ω·cm, magnetic permeability is 2~250.
Citation Information
Patent Citations
Method for preparing ceramic with high Fe2O3 content and high electric conductivity
CN102173735A
Aluminum oxide anti-static ceramic material and preparation method thereof
CN105236941A
Building ceramic tile prepared from fine-grained iron tailing powder and preparation method of building ceramic tile
CN113213890A
Process of preparing heterogenous conducting Si3N4 / Tin ceramic material tail iron ore
CN1887796A
Electroconductive ceramic, antistatic material using the same and magnetic disc device
JP2000313663A